Traditional Values as Background Factor of Contemporary Russian Morals - Galeev Zufar; Kachalov Vadim (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
A systematic study of the existing traditional values makes it possible to identify the contemporary state of Russian morals, as well as the national social and personal behavior patterns. Traditional values are the fundamentals of the contemporary national morality. Their denial and belittling give rise to selfish needs while scattered rights and responsibilities lead to public unwillingness to accept social roles and duties. Traditional values improve personal moral qualities, thus contributing to social and personal ascent. Traditional and innovative values tend to work in a harmonious conjugation. The authors attempted to measure traditional values in relation to innovative ones as to define a harmonious entity that could bring Russian morals to balance. A systematic study of Russian morals and social and personal behavior patterns could reveal the existing value mechanisms. This research featured Russian morals as expressed by university students and young employees. The traditional values that affect the national morals were studied by the means and methods of social sciences and humanities. The systemic approach provided a fresh insight into the problem field that yielded some alternative theoretical generalizations, expanding the socio-humanitarian knowledge and contributing to a better practice of social development.